Trust Management Scheme Based on D-S Evidence Theory for Wireless Sensor Networks - Renjian Feng; Shenyun Che; Xiao Wang; Ning Yu (International Journal of Distributed Sensor Networks)
Trust management scheme has been regarded as a powerful tool to defend against the wide set of security attacks and identify malicious nodes. In this paper, we propose a trust management scheme based on revised Dempster-Shafer (D-S) evidence theory. D-S theory is preponderant in tackling both random and subjective uncertainty in the trust mechanism. A trust propagation mechanism including conditional trust transitivity and dynamic recommendation aggregation is developed for obtaining the recommended trust values from third part nodes. We adopt a flexible synthesis method that uses recommended trust only when no direct trust exists to keep a good trust-energy consumption balance. We also consider on-off attack and bad mouthing attack in our simulation. The simulation results and analysis show that the proposed method has excellent ability to deal with typical network attacks, better security, and longer network lifetime.